PECULIARITIES OF MORPHOMETRIC AND ANATOMICAL CHARACTERISTICS OF SCOTS PINE (PINUS SYLVESTRIS L.) IN THE STAND AFFECTED BY ANNOSUM ROOT ROT - Dyshko, V. A.; Torosova, L. O. (Forestry and Forest Melioration, 2018)
Introduction The set of measures which are used now for the prevention and control of annosum root rot is not effective and does not limit the disease completely. The most realistic way to solve this problem may be the using of high quality seeds harvested from trees highly resistant against pathogens. The aim of the study was to investigate morphological and biometric features of the generative organs and anatomical structure of needles of pine trees for assessing the degree of resistance against annosum root rot and to analyze the effectiveness of their using in preliminary diagnostics. Materials and Methods The study was conducted in mixed pine plantation of V age class according to the guidelines on general principles of forest mensuration and forest pathological surveys. For the investigation, the trees were selected in glades in the disease foci. The trees were different in health condition. The trees of the II and III health condition categories with died tops and the resin flows on the stem were considered as “sick”; the trees of the I and II categories without clear outer signs of the disease (trees of good health status, having dense crown, without signs of needles damage, etc.) were conventionally considered as “stable”. As a control (“healthy” trees) the trees of the I and II categories that grow at a considerable distance from the die-back foci were selected. For all trees the mensuration indicators were measured, morphological and biometric features of cones and seeds were examined; the anatomical structure of needles was studied. For the statistical analysis the average values of the investigated characteristics, their statistical errors and coefficients of variation were used. Results The results of the study showed that “stable” trees were significantly different from the “sick” and “control” ones by a lower height of the stem. Also the significant differences were found in the sizes of the generative organs of investigated “stable” trees and trees of other categories (p ? 0.01). There was no correlation between color of generative organs and resistance of the trees. In the group of “stable” trees, the individuals with hooked apophysis of seed scales of cones and with a larger number of resin channels in the needles dominate. Empty seeds were detected in each of the trees, but their share was different. The length of needles of “healthy” trees was 7 % higher than of “stable” ones and 36 % higher than of “sick” ones. The number of resin channels in needles of the “stable” trees was greater than of “sick” ones; the largest amount of the channels was found in needles of “control” trees. Conclusions The using of biometric parameters of cones, seeds and needles to assess the stability of trees in plantations may be not effective because of the variability of these signs caused by external influences. There were no correlations between colors of generative organs and seeds and the resistance of trees. The information about high resistance of trees with black seeds was not confirmed. Smaller range of variability of the parameters of “sick” trees may indicate the suppression of metabolism intensity and deviation of physiological processes. The individuals with a distinct hooked form of cones’ apophysis and with more resin channels in the needles are dominated among the “stable” trees, In our opinion, the form of seed scale apophysis and the number of resin channels in needles can be used as additional marker characteristics in disease-resistant trees selection because they are genetically fixed.